QUANTIFICATION OF PHENOLICS AND FLAVONOIDS BY SPECTROPHOTOMETER FROM -JUGLANS regia - Asha kale; Sucheta Gaikwad; Kavita Mundhe; Nirmala Deshpande; Jyoti Salvekar (International Journal of Pharma and Bio Sciences, 2010)
Natural antioxidants such as dietary plant phenolics and flavonoids are increasingly attracting attention. They are natural disease-preventing, health-promoting, and anti-ageing substances. Medicinally useful royal Juglans species is worth studying for its traditional therapeutic applications as anticancer, diuretic, anti-inflammatory and laxative effects. It is a rich source of antioxidants i.e. phenolics and flavonoids. Present study involves spectrophotometric determination of phenolics and flavonoids content from chloroform, ethyl acetate, ethanolic and methanolic extracts of walnut bark using Folin-Ciocalteau reagent and Quercetin as standard. The results show high contents of phenolics and flavonoids supporting the antioxidant activity of the extracts and suggest need for further investigations to isolate secondary metabolites.